1992
DOI: 10.1002/ijc.2910500113
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative dot blot analyses of blood‐group‐related antigens in paired normal and malignant human breast tissues

Abstract: Membranes were prepared from 31 breast-cancer specimens and adjacent mammary tissues, dot-blotted to nitrocellulose paper, and reacted with monoclonal antibodies (MAbs) (A, B, Lewis a, Lewis b, sialylated Lewis a, Lewis x, and Lewis y) and lectins (Ulex europaeus, peanut agglutinin) having various blood-group specificities. The expression of epithelial membrane antigen was assayed with MAb MA5. The ratio of breast-cancer to normal mammary membrane preparations (C/N ratios) of these reagents was measured by den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…Conversely to our ®ndings in the rat MT-W9 model, several studies show that loss of expression of A and B antigens occurs during human breast tumour progression, although inappropriate A and B antigen in human mammary carcinomas has been reported in O individuals (Strauchen et al, 1980;Lee et al, 1985;Vowden et al, 1986;Ura et al, 1992). The studies on ABH expression in human mammary tumours re¯ect the fact that we found very few rat tumour cells which express M-N#1 (Table 1), suggesting that the upregulation of M-N#1 in the MT-W9 model may be paralleled in only a small subset of human tumours.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely to our ®ndings in the rat MT-W9 model, several studies show that loss of expression of A and B antigens occurs during human breast tumour progression, although inappropriate A and B antigen in human mammary carcinomas has been reported in O individuals (Strauchen et al, 1980;Lee et al, 1985;Vowden et al, 1986;Ura et al, 1992). The studies on ABH expression in human mammary tumours re¯ect the fact that we found very few rat tumour cells which express M-N#1 (Table 1), suggesting that the upregulation of M-N#1 in the MT-W9 model may be paralleled in only a small subset of human tumours.…”
Section: Discussioncontrasting
confidence: 99%
“…17,31,32 In breast cancer, previous studies have described variable H antigen expression and loss of the A and B antigens, a characteristic shown to increase cell motility. 16,31,33,34 Regarding overall tumor progression, Le Pendu et al 34 hypothesized that the presence of ABH antigens in precancerous epithelial cells may promote resistance to apoptosis, facilitating malignant transformation and escape from immune surveillance, and that at more advanced stages of tumor progression, tumor cells that have lost blood group antigen expression may then demonstrate increased metastatic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Decreased levels of blood group antigens have been detected in breast carcinomas, and altered glycosylation and antigen expression has been implicated in the invasiveness of breast cancer, although the prognostic value of this is still uncertain. [15][16][17][18] Triple-negative breast cancer (TNBC), defined as the lack of expression of the estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) proteins, accounts for approximately 10-20 % of breast cancers. [19][20][21] TNBC has been associated with higher histological grade and larger tumor size at diagnosis, and patients generally have a shorter diseasefree interval and poorer overall survival.…”
mentioning
confidence: 99%
“…A blood-group-related carbohydrate, the Y difucosylated hapten (Lewis Y antigen), also designated as a cluster-6 antigen on lung tumor cells [28], is associated with 60-90% of human tumors of epithelial origin, including breast, colon, and gastric cancer, and SCLC [45][46][47][48]. Its level of expression correlates with survival in patients with lung cancer [49].…”
Section: Lewis Y Antigenmentioning
confidence: 99%